Optical spherical electromotive density with some fractional applications with Laplace transform in spherical Heisenberg space SH2 - Körpınar, Talat; Körpınar, Zeliha (Elsevier GmbH, 2021)
In this paper, we construct a new theory of spherical electromotive force of spherical Ss −magnetic flows with the spherical frame in spherical Heisenberg space SH2. Also, we obtain some optical conditions of spherical Ss −magnetic Lorentz flux by using optical spherical fields in spherical Heisenberg space SH2. Moreover, we give some applications of spherical Heisenberg electromotive forces fEϕαH,fEϕtH,fEϕsH for spherical vector fields. Additionally, we compute representation of spherical curvatures of spherical Ss −magnetic flows by considering Heisenberg spherical ferromagnetic spin in spherical Heisenberg space SH2. Finally, spherical Heisenberg electromotive forces fEϕαH,fEϕtH,fEϕsH are given in a static and uniform magnetic surface with the q -Homotopy analysis transform method in spherical Heisenberg space SH2. © 2021 Elsevier GmbH
Keywords: Geometric magnetic flux density; Heisenberg ferromagnetic spin; Laplace transform (LT); q -homotopy analysis transform method; Spherical frame; Spherical Heisenberg electromotive force